THE IMPACT OF MOTIVATION IN LEARNING FOREIGN LANGUAGES - Tilavova, Malika (Журнал иностранных языков и лингвистики, 2021)
This article deals with the role of motivation to acquire a foreign language as well as identifying the type of motivation which create effective learning process. One of the most important tasks of a teacher is to increase motivation to learn English, to try to find an optimal way for each teacher to solve the task, to use traditional ways and methods of influencing students to get acquainted with the culture of the country under research , one of the most effective technologies, game technology and others will be covered in this article.